Development of Novel Implantable Intraocular Pressure Sensors to Enhance the Performance in in vivo Tests - Shin, Kyeong-Sik; Jang, Cheol-In; Kim, Mi Jeung; Yun, Kwang-Seok; Park, Ki Ho; Kang, Ji Yoon; Lee, Soo Hyun (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2015)
In this paper, we proposed a dual-mode intraocular pressure (IOP) sensor that has two separated diaphragms to conduct the changes of inductance and capacitance, and we compared the sensor's performance with that of the conventional single variable capacitive sensor (single-mode sensor). Both mode sensors were used to monitor the pressure in in vitro tests with multiple media and in in vivo tests with rabbits. First, we demonstrated that the sensitivities of two types of sensors tended to be different for in vivo and in vitro tests. This was the first known attempt to show changes in the sensitivity and responsivity of IOP sensors in in vivo tests. The sensitivity and phase dip of the dual-mode sensor exceeded that of the single-mode sensor, irrespective of medium due to isolation of capacitive sensor from medium. In this paper, we have provided the equations that were used to evaluate the improvement in sensitivity, and we have shown the coincidence with in vitro and in vivo tests. Based on the results we achieved, we believe that the dual-mode sensor is more feasible for use as an IOP sensor in in vivo tests, because its responsivity and sensitivity are superior to those of the conventional sensors. [2014-0379]
Keywords: GOLDMANN APPLANATION TONOMETER; TONO-PEN